2016
DOI: 10.1099/ijsem.0.000947
|View full text |Cite
|
Sign up to set email alerts
|

Caldimicrobium thiodismutans sp. nov., a sulfur-disproportionating bacterium isolated from a hot spring, and emended description of the genus Caldimicrobium

Abstract: A novel autotrophic, thermophilic bacterium, strain TF1 T , was isolated from a hot spring in Japan. Cells of strain TF1 T were motile, Gram-stain-negative, rod-shaped, 1.0-2.0 mm in length and 0.5-0.6 mm in width. Major components in the cellular fatty acid profile were C 16 : 0 , C 18 : 0 and anteiso-C 17 : 0 . The temperature range for growth was 40-77 8C, and optimum temperature was 75 8C. The pH range for growth was 5.9-9.5, and the optimum pH was 7.5-8.8. Strain TF1 T grew chemolithoautotrophically by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…The next most abundant CODH/ACS sequences had read depths of 68× and 24×; these sequences belonged to two different potential members of the Planctomycetes , one representing OTU-14 (see below), and the other a less abundant member of the undermat layer that was not identified by 16S rRNA (Thiel et al, 2016). The least abundant CODH/ACS gene belonged to a member of the Thermodesulfobacteriaceae (OTU-26), a relative of Caldimicrobium thiodismutans , for which autotrophic growth by hydrogen oxidation or disproportionation of sulfur compounds has been demonstrated (Kojima et al, 2016). Two copies of CODH/ACS sequences were affiliated with Thermodesulfovibrio sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next most abundant CODH/ACS sequences had read depths of 68× and 24×; these sequences belonged to two different potential members of the Planctomycetes , one representing OTU-14 (see below), and the other a less abundant member of the undermat layer that was not identified by 16S rRNA (Thiel et al, 2016). The least abundant CODH/ACS gene belonged to a member of the Thermodesulfobacteriaceae (OTU-26), a relative of Caldimicrobium thiodismutans , for which autotrophic growth by hydrogen oxidation or disproportionation of sulfur compounds has been demonstrated (Kojima et al, 2016). Two copies of CODH/ACS sequences were affiliated with Thermodesulfovibrio sp.…”
Section: Resultsmentioning
confidence: 99%
“…Three low abundance partial dsrAB sequences (16–26 × coverage) showed closest similarity to Caldimicrobium thiodismutans with 87–93% amino acid identity and 96–98% similarity (Table S13). C. thiodismutans has recently been isolated from a hot spring in Japan and displays sulfur disproportionating activity (Kojima et al, 2016). A similar sulfur-disproportionating metabolism is hypothesized for the Mushroom Spring mat member (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Various lineages affiliated to Thermotogales and Desulfurococcales can use elemental sulfur and polysulfide as electron acceptor (Erauso et al, 1993;González et al, 1998;Adams et al, 2001;Huber and Stetter, 2006;Gorlas et al, 2015) whereas Caldimicrobium, identified in large proportion in the deepest sediment layers (Figure 4 and Table S5), can disproportionate elemental sulfur and generate sulfate and hydrogen sulfide as described for Caldimicrobium thiodismutans sp. nov (Kojima et al, 2016). Polysulfide and elemental sulfur are likely to be abundant in the hydrothermal fluid where dissolved sulfide can abiotically react with iron or manganese, detected in the Guaymas Basin hydrothermal fluid (Von Damm et al, 1985).…”
Section: Hydrothermal Influence Leads To Contrasted Microbial Communitymentioning
confidence: 99%
“…C . thiodismutans has been shown to couple autotrophic growth to disproportionation of S°, S 2 O 3 2− and SO 3 2− but not reduction of SO 4 2− (Kojima et al ., ). It has been suggested that during sulphur disproportionation, S 2 O 3 2− and S° are first converted to SO 3 2− by thiosulfate reductase and a yet to be defined enzyme, respectively (Finster, ).…”
Section: Resultsmentioning
confidence: 99%
“…The most abundant bacterial MAG (6% of the EP community) is affiliated with Caldimicrobium thiodismutans (80% ID), a strain that has yet to be reported in a YNP hot spring system, let alone to be dominant among the bacterial component of a YNP community. C. thiodismutans has been shown to couple autotrophic growth to disproportionation of S , S 2 O 3 2− and SO 3 2− but not reduction of SO 4 2− (Kojima et al, 2016). It has been suggested that during sulphur disproportionation, S 2 O 3 2− and S are first converted to SO 3 2− by thiosulfate reductase and a yet to be defined enzyme, respectively (Finster, 2008).…”
Section: Taxonomic and Functional Composition Of The Ep Sediment Commmentioning
confidence: 99%